ANALYSIS OF SCIENCE PROCESS SKILLS OF GRADE V STUDENTS OF PRIVATE ELEMENTARY SCHOOLS IN KEMIRI SUB-DISTRICT - Mar'atus Sholihah, Nur Ngazizah, Rintis Rizkia (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This study aims to analyze the science process skills of fifth grade students of one of the private elementary schools in Kemiri sub-district. The type of research used is qualitative with the research design is historical research. The subjects of this study were fifth grade students of one of the private elementary schools in Kemiri sub-district in the 2023/2024 school year with a total of 6 students taken from high, low, and medium abilities. Data collection techniques in this study using observation, questionnaires, interviews and documentation. Data analysis was carried out, namely, data reduction, data display, and conclusions. The results of this study obtained that the science process skills of fifth grade students of one of the private elementary schools in Kemiri sub-district are in the proficient category. With a description of each indicator of science process skills, namely: 1) observing is in the proficient category, 2) predicting in the proficient category, 3) classifying in the proficient category, 4) interpreting in the proficient category, 5) concluding in the proficient category, and 6) communicating in the decent category. It is expected that teachers carry out science learning by optimizing existing indicators in science process skills through questions and practices or experiments that meet the indicators of science process skills so that students have skills that are useful for their daily lives.